Desenvolvimento de um sistema de conversão e colheita de energia para estudo das propriedades piezoelétricas do BaTiO3 obtido por síntese sonoquímica - Monteiro, Sioney Teixeira (Brasil, 2023)
Energy harvesting using piezoelectric materials has attracted attention due to their excellent electromechanical conversion properties. With growing concerns about environmental issues in traditional lead-based piezoelectric materials, it is imperative to develop lead-free piezoelectric alternatives. The Barium Titanate BaTiO3, is known in the technological ceramics industry due to its piezoelectric properties, being an auspicious material to oppose the current materials with lead in its composition. However, the most used methods of synthesis can affect its ferroelectric properties or are complex and costly. Due to its characteristics, sonochemical synthesis is a simple and fast alternative to obtain BaTiO3 under ambient temperature and pressure conditions. In this study, we present an energy conversion device to evaluate the piezoelectric performance of samples of Barium Titanates obtained by the sonochemical method with a sonication time of 15 minutes compared to the sample obtained by the Pechini method. The study allowed investigating the influence of this synthesis on the structural properties and how these influence the electrical properties of BaTiO3. The samples were characterized by X-ray diffraction technique, where we obtained high crystallinity, scanning electron microscopy with particles below 1 μm and the presence of other larger clusters, energy dispersive spectroscopy with the atomic ratio between Ba/Ti elements of 1.14, complex impedance spectroscopy with maximum values of electrical resistance and relaxation of 1.37x106 Ω and 4.493x10-4 s, respectively, Archimedes density with mean density of 3.6805 g cm-3 and micro electromechanical system (MEMS ). The output voltage is taken as the parameter to verify the performance of the piezoelectric samples, where we obtained a maximum output voltage of 184 Mv.